CARDIOTROPHIN-1 AS AN INDEPENDENT FACTOR OF EARLY DEVELOPMENT OF ATHEROSCLEROTIC CHANGES IN COMORBID PATIENTS - Bilovol, O.M.; Dunaieva, I.P. (World of Medicine and Biology, 2025)
The work is devoted to the study of cardiotrophin-1 as a crucial biomarker for the early development of atherosclerotic changes in patients with comorbid conditions, such as arterial hypertension, type 2 diabetes mellitus, and obesity. Considering the high prevalence of these conditions, the early detection of factors contributing to cardiovascular complications is of paramount importance. The study included 211 patients aged 49 to 65 years, divided into four groups based on the presence of arterial hypertension, type 2 diabetes mellitus, and obesity. The results show a significant increase in the level of cardiotrophin-1in patients with comorbid pathology compared to healthy individuals. The study found that cardiotrophin-1is not only an indicator of early cardiovascular complications but also a prognostic factor for the development of atherosclerosis. A positive correlation between cardiotrophin-1 levels and the atherogenic index was also established in all patient groups.
Keywords: cardiotrophin-1; arterial hypertension; type 2 diabetes mellitus; obesity; atherosclerosis; comorbid conditions; biomarkers